Protective and enhancing HLA alleles, HLA-DRB1*0901 and HLA-A*24, for severe forms of dengue virus infection, dengue hemorrhagic fever and dengue shock syndrome. - Thi Phuong Lan Nguyen; Mihoko Kikuchi; Thi Que Huong Vu; Quang Ha Do; Thi Thuy Tran; Dinh Tham Vo; Manh Tuan Ha; Van Tuong Vo; Thi Phi Nga Cao; Van Dat Tran; Toshifumi Oyama; Kouichi Morita; et al. (Public Library of Science (PLoS), 2008)
BACKGROUND: Dengue virus (DV) infection is one of the most important mosquito-borne diseases in the tropics. Recently, the severe forms, dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS), have become the leading cause of death among children in Southern Vietnam. Protective and/or pathogenic T cell immunity is supposed to be important in the pathogenesis of DHF and DSS. METHODOLOGY/PRINCIPAL FINDINGS: To identify HLA alleles controlling T cell immunity against dengue virus (DV), we performed a hospital-based case control study at Children's Hospital No.2, Ho Chi Minh City (HCMC), and Vinh Long Province Hospital (VL) in Southern Vietnam from 2002 to 2005. A total of 211 and 418 patients with DHF and DSS, respectively, diagnosed according to the World Health Organization (WHO) criteria, were analyzed for their characteristic HLA-A, -B and -DRB1 alleles. Four hundred fifty healthy children (250 from HCMC and 200 from VL) of the same Kinh ethnicity were also analyzed as population background. In HLA class I, frequency of the HLA-A*24 showed increased tendency in both DHF and DSS patients, which reproduced a previous study. The frequency of A*24 with histidine at codon 70 (A*2402/03/10), based on main anchor binding site specificity analysis in DSS and DHF patients, was significantly higher than that in the population background groups (HCMC 02-03 DSS: OR = 1.89, P = 0.008, DHF: OR = 1.75, P = 0.033; VL 02-03 DSS: OR = 1.70, P = 0.03, DHF: OR = 1.46, P = 0.38; VL 04-05 DSS: OR = 2.09, P = 0.0075, DHF: OR = 2.02, P = 0.038). In HLA class II, the HLA-DRB1*0901 frequency was significantly decreased in secondary infection of DSS in VL 04-05 (OR = 0.35, P = 0.0025, Pc = 0.03). Moreover, the frequency of HLA-DRB1*0901 in particular was significantly decreased in DSS when compared with DHF in DEN-2 infection (P = 0.02). CONCLUSION: This study improves our understanding of the risk of HLA-class I for severe outcome of DV infection in the light of peptide anchor binding site and provides novel evidence that HLA-class II may control disease severity (DHF to DSS) in DV infection.